Counterterrorism in the west and the challenges it presents to human rights. (c2017) - Rayes, Nour Asmat (2017)
Violent extremism has been a security concern for countries worldwide, especially following the attacks on September 11th, 2001. Since then, the face of counterextremism has changed, and human rights principals have been traded in for security. This thesis aims to pursue a better understanding of how breaching human rights in the battle against violent extremism will backfire by increasing the number of violent extremist fighters, and thus increasing the number of violent extremist attacks. During this crucial time in which violent extremism is spreading and gaining strength, it is important for governments to understand the impact of the quality of their counterextremism policies, and the importance of maintaining their ideologies and respect for human rights. It is in times of crises that states should most respect international law.